A Single-Stage 0X/1X Regulating Rectifier With Improved Voltage Mode Delay Compensation for Wirelessly Powered Implantable Medical Devices - Silong Chen; Guangyin Shi; Xin Liu; Xingchen Xu; Bin Wang; Zhiqiang Li (IEEE Access)
This article presents a 6.78 MHz single-stage wireless power transfer (WPT) receiver (RX) using 0X/1X regulating rectifier with improved voltage mode (VM) delay compensation for implantable medical devices (IMDs). The regulation of 0X/1X modes is achieved through pulse width modulation (PWM), with the frequency set at 1/16 of the carrier clock to ensure circuit stability and enhance power conversion efficiency (PCE) under light loads. VM delay compensation has the advantage of power consumption. However, the traditional VM on-delay compensation may become ineffective because a large voltage pulse will occur on the RX side input when the circuit delays increase. Therefore, an improved VM on-delay compensation method is proposed. Coarse compensation for on-delays can be achieved by reusing the control signal generated from off-delay compensation loop, as off-delay compensation processes will not be influenced by on-delay compensation processes. It allows the on-delay compensation loop to function normally and finely compensate for on-delays. The proposed rectifier is designed in $0.18μ $ m CMOS process. It can achieve output voltage management of 1.8V. Comparing with other regulating rectifier, the proposed rectifier has a fast transient response of $14~μ $ s and a small chip area of 0.91 mm2. The simulation results indicate that this rectifier can attain high PCE of 84.6% in light load ( $500Ω $ ) and peak PCE of 93.5% in heavy load ( $50Ω $ ). The high voltage conversion ratio (VCR) of over 93% is also achieved under the large circuit delays.